Revitalization, transformation and the 'Bilbao effect': testing the local area impact of iconic architectural developments in North America, 2000–2009. Issue 1 (2nd January 2022) - Patterson, Matt
ABSTRACT: The term 'Bilbao effect' describes the potential of iconic architectural developments (IADs) designed by world famous architects to act as a catalyst for economic revitalization and transformation within neighbourhoods or regions. Despite the ubiquity of this term, its validity is still debated. Furthermore, research on the topic has relied almost exclusively on individual or small-N comparative case studies. This paper builds on this research by testing the Bilbao effect through a quantitative analysis of 142 IADs completed in Canada and the United States between 2000 and 2009. Using fixed effects modelling, a method that controls for selection bias, the analysis examines the effect of IADs on a set of outcome variables that measure neighbourhood-level economic and cultural changes during this period: population, rent, the number of local arts establishments and the number of cultural workers living in the area. The analysis demonstrates that neighbourhoods with IADs generally experienced more economic and cultural growth than non-IAD neighbourhoods during this time period. However, the paper also complicates these findings by examining differences in how this growth manifests itself within emerging versus established neighbourhoods. These differences are illustrated through a comparison of the Dallas Arts District and Lincoln Square, Manhattan.